ANALISIS RESPON PEMILIH PEMULA DALAM MENANGGAPI ISU BLACK CAMPAIGN PADA PLATFORM MEDIA SOSIAL SAAT KAMPANYE CALON PRESIDEN DAN WAKIL PRESIDEN:(Studi Kasus Pada Pemilih Pemula Alumni SMA Pangudi Luhur Jakarta Selatan Angkatan 2018 Dalam Menanggapi Isu Black Campaign Yang Bersifat Fitnah Dan Provokatif Di Platform Media Sosial Saat Pemilihan Umum 2019) - Giovani Abel Melando (2022)
This paper examines novice voters in responding to the issue of black campaigns on social media during the campaign for presidential and vice presidential candidates in the 2019 general election. Social media platforms as one of the supporting facilities for campaigning of course have a lot of positive and negative campaigns among the public. . In this case study, their role is needed to see and address black campaign issues that are slanderous and provocative as well as to see the negative issues that occur as well as their views on whether these issues are a setback for our democratic life. By using qualitative descriptive methods through interviews and literature studies, this paper discusses their perception as novice voters among the alumni of Pangudi Luhur High School South Jakarta Batch 2018 in looking at black campaign issues that often occur on social media during presidential and presidential candidate campaigns. vice president in the 2019 general election yesterday.